PERILAKU POLYAMORY DALAM HUBUNGAN PERNIKAHAN PERSPEKTIF HUKUM POSITIF DI INDONESIA - Sucianti, Nur; Alghiffary, Muhammad (Islamic Studies Journal for Social Transformation, 2025)
This study aims to understand the concept of polyamory behavior in marriage from the perspective of applicable law in Indonesia. Methodologically, this research uses a qualitative method with a normative approach supported by a literature study that examines polyamory in the perspective of Indonesian positive law, with data collection through the study of scientific journals, books, and previous legal documents. The results show that polyamory behavior in the context of marriage is not in line with the concept of monogamous marriage commonly embraced by Indonesian society. Therefore, from a legal perspective, polyamory behavior has no legality and contradicts the principle of monogamy as stipulated in Law Number 1 Year 1974 and the Civil Code. The theoretical implication shows that law functions as a tool to regulate community behavior in order to achieve social stability. Practically, this study provides an overview of how Indonesian law responds to polyamory behavior. This article contributes to the development of an understanding of polyamory behavior in marriage, from the perspective of positive law in Indonesia.